Hari Akhir Pada Pendidikan Agama Islam Melalui Metode Card Sort Dengan Model PBL (Problem Based Learning) Pada Peserta Didik Kelas V SDN 27 Salibawan Kec. Lubuk Sikaping - Wanis, Wirda (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the understanding and learning outcomes of fifth-grade students at SDN 27 Salibawan regarding belief in the Last Day through the implementation of the Card Sort method with the Problem-Based Learning (PBL) model. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The results indicate that in Cycle I, 53.8% of students achieved learning mastery, while in Cycle II, 84.6% of students reached mastery. Additionally, student engagement showed a significant increase from Cycle I to Cycle II. This study concludes that the application of the Card Sort method with the PBL model is effective in improving students’ understanding, learning outcomes, and engagement in learning about belief in the Last Day.